2010
DOI: 10.1111/j.1525-142x.2010.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Are palaeoscolecids ancestral ecdysozoans?

Abstract: The reconstruction of ancestors is a central aim of comparative anatomy and evolutionary developmental biology, not least in attempts to understand the relationship between developmental and organismal evolution. Inferences based on living taxa can and should be tested against the fossil record, which provides an independent and direct view onto historical character combinations. Here, we consider the nature of the last common ancestor of living ecdysozoans through a detailed analysis of palaeoscolecids, an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 116 publications
(196 reference statements)
6
150
0
4
Order By: Relevance
“…From a theoretic point of view, the stronger primary biomineralization of sclerites by phosphate in frequently moulting lobopodians is also less likely because phosphatization involves high-energy costs, and moulting would regularly cause a loss of these biomineralized structures. Recent phylogenetic analyses of palaeoscolecidans have also considered Tabelliscolex and Cricocosmia as belonging to a sister clade of the palaeoscolecidans sensu stricto (Harvey et al 2010). If the homology for the sclerites in this clade and those of lobopodians can further be supported, the existence of net-like trunk sclerites may be considered as a synapomorphic character for the ecdysozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretic point of view, the stronger primary biomineralization of sclerites by phosphate in frequently moulting lobopodians is also less likely because phosphatization involves high-energy costs, and moulting would regularly cause a loss of these biomineralized structures. Recent phylogenetic analyses of palaeoscolecidans have also considered Tabelliscolex and Cricocosmia as belonging to a sister clade of the palaeoscolecidans sensu stricto (Harvey et al 2010). If the homology for the sclerites in this clade and those of lobopodians can further be supported, the existence of net-like trunk sclerites may be considered as a synapomorphic character for the ecdysozoa.…”
Section: Discussionmentioning
confidence: 99%
“…If the homology for the sclerites in this clade and those of lobopodians can further be supported, the existence of net-like trunk sclerites may be considered as a synapomorphic character for the ecdysozoa. The recent review of anatomy and phylogenetic analysis of the palaeoscolecidans by Harvey et al (2010) revealed a stem-priapulid or nematomorph position for the palaeoscolecidans that is more remote to the panarthropodans. However, their cladistic analysis did not appear extremely robust and the phylogenetic position of the palaeoscolecidans was strongly influenced by the inclusion of different fossil clades, such as genera of extinct cycloneuralians (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1). Priapulids are another clade that likely evolved carnivory around the ProterozoicCambrian transition, although the timing can only currently be constrained between their divergence from kinorhynchs and the appearance of early Cambrian predatory forms (21), as the Priapulida crown group is undated and it is unclear whether the small nonpredatory forms at the base of this clade in morphological cladistics trees (22) represent the primitive form or are derived from a larger, potentially carnivorous ancestor. Molecular clock ages for nodes constraining the evolution of carnivory (2,23) clearly suggest that bilaterians originated long before carnivory evolved within the clade around the Proterozoic-Cambrian transition (Fig.…”
mentioning
confidence: 99%
“…The cross-section of a well-preserved sclerite (Figure 8.3) allows identification of chlorite distribution in a selective way, depending on porosity or cracking in each surface area so that, in BSE analyses, chlorites (recognisable by mapping of Fe and Mg in yellow and white, respectively, Figure 8.4), are preferably located covering the tuberculated surface and the base of the marginal brim. In contrast, pristine apatite (see mapping of P and Ca elements in turquoise and white, respectively), which could represent the primary biomineral cuticle of the palaeoscolecids (Harvey et al, 2010), forms the surface of the middle surface and the marginal brim. As a result, the preservation after diagenetic mineral replacement can be explained by its nonporous and massive character: the resulted phosphatic parts of the sclerite were less susceptible to be damaged by abrasion and affected by cement occlusion.…”
Section: Taphonomic Constraintsmentioning
confidence: 99%
“…They were common components of Cambrian-Late Silurian marine benthic communities 1997;García-Bellido et al, 2013;Hou and Bergström, 1994;Kraft and Mergl, 1989;Müller and Hinz-Schallreuter, 1993;Zhang and Pratt, 1996). Despite the finding of complete and well-preserved palaeoscolecidan cuticles in the lower Cambrian Chengjiang Lagerstätte of China (Hou and Bergström, 1994;Zhang and Pratt, 1996), the middle Cambrian of Australia (Müller and Hinz-Schallreuter, 1993), and the Lower Ordovician of Bohemia (Hinz et al, 1990), some aspects related to both their phylogenetic relationships with ecdysozoan groups and lifestyle are still under discussion (Botting et al, 2012;Conway Morris and Peel, 2010;Han et al, 2007aHan et al, , 2007bHan et al, , 2007cHarvey et al, 2010;Wills et al, 2012).…”
Section: Introductionmentioning
confidence: 99%